Looking through Providers' Eyes: Pain in the Neonatal Intensive Care Unit - Borten, Julia B.L.; Barros, Marina C.M.; Silva, Erica S.; Carlini, Lucas P.; Balda, Rita C.X.; Orsi, Rafael N.; Heiderich, Tatiany M.; Sanudo, Adriana; Thomaz, Carlos E.; Guinsburg, Ruth (American Journal of Perinatology, 2023)
Objective Evaluate the pain of critically ill newborns is a challenge because of the devices for cardiorespiratory support. This study aim to verify the adults' gaze when assessing the critically ill neonates' pain at bedside.Study Design Cross-sectional study in which pediatricians, nursing technicians, and parents evaluated critically ill neonates' pain at bedside, for 20 seconds with eye-tracking glasses. At the end, they answered whether the neonate was in pain or not. Visual tracking outcomes: number and time of visual fixations in four areas of interest (AOI) (face, trunk, and upper [UL] and lower [LL] limbs) were compared between groups and according to pain perception (present/absent).Results A total of 62 adults (21 pediatricians, 23 nursing technicians, 18 parents) evaluated 27 neonates (gestational age: 31.8 ± 4.4 weeks; birth weight: 1,645 ± 1,234 g). More adults fixed their gaze on the face (96.8%) and trunk (96.8%), followed by UL (74.2%) and LL (66.1%). Parents performed a greater number of fixations on the trunk than nursing technicians (11.0 vs. 5.5 vs. 6.0; p = 0.023). Controlled for visual tracking variables, each second of eye fixation in AOI (1.21; 95% confidence interval [CI]: 1.03–1.42; p = 0.018) and UL (1.07; 95% CI: 1.03–1.10; p < 0.001) increased the chance of perceiving the presence of pain.Conclusion Adults, when assessing at bedside critically ill newborns' pain, fixed their eyes mainly on the face and trunk. The time spent looking at the UL was associated with the perception of pain presence.Key Points
Keywords: infant; newborn; pain measurement; intensive care units; neonatal; eye-tracking technology; fixation; ocular